1997
DOI: 10.1002/pro.5560060308
|View full text |Cite
|
Sign up to set email alerts
|

A 3D model for the measles virus receptor CD46 based on homology modeling, Monte Carlo simulations, and hemagglutinin binding studies

Abstract: The two terminal complement control protein (CCP) modules of the CD46 glycoprotein mediate measles virus binding. Three-dimensional models for these two domains were derived based on the NMR structures of two CCP modules of factor H. Both CD46 CCP modules are about 35 8, long, and form a five-stranded antiparallel P-barrel structure. Monte Carlo simulations, sampling the backbone torsion angles of the linker peptide and selecting possible orientations on the basis of minimal solvent-exposed hydrophobic area, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 48 publications
(45 reference statements)
3
34
0
Order By: Relevance
“…24)). This same region has been implicated in MV binding by multiple groups (24,25,27,36,37). Thus, these results point to a second site in MCP, encompassing amino acids 94 -103, important for both C4b and MV interactions.…”
Section: Resultsmentioning
confidence: 56%
“…24)). This same region has been implicated in MV binding by multiple groups (24,25,27,36,37). Thus, these results point to a second site in MCP, encompassing amino acids 94 -103, important for both C4b and MV interactions.…”
Section: Resultsmentioning
confidence: 56%
“…Proteins-Mutagenesis studies in the CD46 CCP-I-II modules revealed that exchange of short peptide segments often resulted in loss of surface expression and in reduced reactivity to several CD46 mAbs, suggesting impaired protein folding (27). To minimize folding problems, we opted for a mutagenesis technique based on replacement of single amino acids by small residues (alanine for charged and polar, serine for apolar residues), thus likely allowing maintenance of the …”
Section: Cell Surface Expression Of 40 Single Amino Acid Ccp-i-ii Mutantmentioning
confidence: 99%
“…We previously approached the definition of the primary MV binding site by H protein binding studies based on a threedimensional model of CCP-I-II (27). The three-dimensional model was based on the NMR structure of the CCP modules from another member of the RCA protein family, the human complement factor H. Each of the two CD46 modules is predicted to be about 35 Å long and to form a five-stranded ␤-barrel structure (27).…”
mentioning
confidence: 99%
See 2 more Smart Citations